EXPERIMENTAL STUDY ON THE LOOSENING LIFE OF BOLTS - JIANG ShiLin; YANG GuangWu; XIAO ShouNe; WANG ChangKe (Jixie qiangdu)
In order to study the loosening life characteristics of bolts, the transverse vibration test of bolts was designed by using fatigue testing machine. The test compared the influence of displacement, velocity and acceleration to the loose of bolts by changing the frequency of transverse vibration. It shows that the transverse displacement amplitude is the main factor influencing the loosening of bolts. The loosening of bolts under five displacement amplitude were measured. The situations of loosening were showed by the rest preload-vibration times curves. Summarized the data, according to the S-N curve, drew the displacement-life（D-N） curve under different loosening situation（the percentage of the residual preload）. The results show: By the D-N curve, it is found that the bolt loosening life curve also have the characteristics of double straight line and high-low cycle, just like the material fatigue life curve.